1998
DOI: 10.1128/jvi.72.5.4472-4477.1998
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy in Mice of Influenza B Virus Vaccines Grown in Mammalian Cells or Embryonated Chicken Eggs

Abstract: The immunogenicity and protective efficacy of formalin-inactivated influenza B/Memphis/1/93 virus vaccines propagated exclusively in Vero cells, MDCK cells, or embryonated chicken eggs (hereafter referred to as eggs) were investigated. Mammalian cell-grown viruses differ from the egg-grown variant at amino acid position 198 (Pro/Thr) in the hemagglutinin gene. The level of neuraminidase activity was highest in egg-grown virus, while MDCK and Vero cell-derived viruses possessed 70 and 90% less activity, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…being ordered in advance or to an avian outbreak reducing the supply of eggs. In addition, it has been shown in animal studies that vaccines produced in mammalian tissue culture can be more protective than those grown in eggs, [44][45][46] an advantage in a pandemic situation. Further studies are required to determine whether this is the case for the RD3 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…being ordered in advance or to an avian outbreak reducing the supply of eggs. In addition, it has been shown in animal studies that vaccines produced in mammalian tissue culture can be more protective than those grown in eggs, [44][45][46] an advantage in a pandemic situation. Further studies are required to determine whether this is the case for the RD3 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…There are few alternative models in mice and ferrets (McLaren, Potter et al 1974;Alymova, Kodihalli et al 1998), but better models are required since anatomical and physiological relevance are as important as immunological relevance. Rabbits, non-human primates and pigs are considered anatomically and physiologically relevant (Ivins, Pitt et al 1998;Macklin, McCabe et al 1998;Little, Ivins et al 2006), but their use in influenza challenge studies is as yet unproven.…”
Section: Future Workmentioning
confidence: 99%
“…The cell culture-based approach involves production of influenza viruses in cell culture followed by the current (egg-based) virus inactivation and purification for the down stream processing. The advantages are: cell cultures are easier to handle and can be scaled up in a short period of time, and the influenza vaccines produced with this approach have been tested in Phase I and Phase II clinical trials and were found to be safe and at least as effective as the vaccines produced in embryonated chicken eggs [13][14][15]. A limitation of the cell culture-based approach is that the process still requires the production of a high-yielding re-assorted virus.…”
Section: Introductionmentioning
confidence: 99%